An Open-Label Pilot Study of Combined Augmentation With Creatine Monohydrate and 5-Hydroxytryptophan for Selective Serotonin Reuptake Inhibitor– or Serotonin-Norepinephrine Reuptake Inhibitor–Resistant Depression in Adult Women. Issue 5 (October 2017) - Kious, Brent M.; Sabic, Hana; Sung, Young-Hoon; Kondo, Douglas G.; Renshaw, Perry
Abstract: Purpose: Many women with major depressive disorder (MDD) respond inadequately to standard treatments. Augmentation of conventional antidepressants with creatine monohydrate and 5-hydroxytryptophan (5-HTP) could correct deficits in serotonin production and brain bioenergetics associated with depression in women, yielding synergistic benefit. We describe an open-label study of 5-HTP and creatine augmentation in women with MDD who had failed selective serotonin reuptake inhibitor (SSRI) or serotonin-norepinephrine reuptake inhibitor (SNRI) monotherapy. Methods: Fifteen women who were adequately adherent to an SSRI or SNRI and currently experiencing MDD, with a 17-item Hamilton Depression Rating Scale (HAM-D) score of 16 or higher, were treated with 5 g of creatine monohydrate daily and 100 mg of 5-HTP twice daily for 8 weeks, with 4 weeks of posttreatment follow-up. The primary outcome was change in mean HAM-D scores. Results: Mean HAM-D scores declined from 18.9 (SD, 2.5) at pretreatment visits to 7.5 (SD, 4.4) ( P < 0.00001), a decrease of 60%. Participants did not experience any serious treatment-related adverse events. Conclusions: Combination treatment with creatine and 5-HTP may represent an effective augmentation strategy for women with SSRI- or SNRI-resistant depression. Given the limitations of this small, open-label trial, future study in randomized, placebo-controlled trials is warranted.